Penerapan Metode Tahfidz Dalam Pembelajaran Al-Qur'an Di Sekolah Islam: Ma Tahfizul Qur'an Nurul Azmi - Muhammad Fikri Iadwaree (Journal of Sustainable Education, 2026)
This study aims to describe the application of the tahfidz method in learning the Qur'an at MA Tahfizul Qur'an Nurul Azmi and identify supporting and inhibiting factors. The study used a descriptive qualitative approach with data obtained through observation, interviews, and documentation of the principal, tahfidz teachers, and students. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the tahfidz method is implemented in a structured manner through memorization, murojaah, talaqqi, and tahsin activities of the Qur'an. The program implementation is supported by a regular schedule, competent teacher guidance, and a conducive school environment. Supporting factors include student motivation, parental support, and a systematic tahfidz program. Inhibiting factors include differences in students' memorization abilities, lack of consistency in murojaah, and time constraints between academic activities and tahfidz. The study concluded that the implementation of the tahfidz method has been running well and has contributed positively to improving students' memorization of the Qur'an, so it is necessary to strengthen murojaah, improve teacher competence, and have closer cooperation between schools and parents.